2017
DOI: 10.1111/cbdd.12956
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis and cytotoxic evaluation of nitric oxide‐releasing derivatives of isosteviol

Abstract: Twenty-six novel isosteviol derivatives coupled with two types of nitric oxide (NO) donors (furoxans and NONOates) were synthesized and screened for cytotoxic activities against four human cancer cell lines with sunitinib as the positive control. The results showed that seven furoxan-based derivatives (8a, 8b, 8c, 8d, 8e, 9e, and 9f) exhibited desirable cytotoxic activities, while NONOate-based derivatives displayed poor potency because of unstability. Compared with sunitinib, compounds 8a and 8e were more act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Different observations showed that these derivatives encouraged apoptosis in HepG2 cells, blocked angiogenic signaling and it didn’t cause toxicity in the treated hosts [85]. Another researcher used the same approach, synthesizing twenty-six novel isosteviol derivatives coupled with two types of nitric oxide (NO) donors (furoxans and NONOates) [86]. Seven of the furoxan based derivatives were tested for their in vitro cytotoxic activity against four cancer cell lines HCT116, Huh7, HepG2, and SW620, while the NONOates displayed negative result [86].…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…Different observations showed that these derivatives encouraged apoptosis in HepG2 cells, blocked angiogenic signaling and it didn’t cause toxicity in the treated hosts [85]. Another researcher used the same approach, synthesizing twenty-six novel isosteviol derivatives coupled with two types of nitric oxide (NO) donors (furoxans and NONOates) [86]. Seven of the furoxan based derivatives were tested for their in vitro cytotoxic activity against four cancer cell lines HCT116, Huh7, HepG2, and SW620, while the NONOates displayed negative result [86].…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
“…Another researcher used the same approach, synthesizing twenty-six novel isosteviol derivatives coupled with two types of nitric oxide (NO) donors (furoxans and NONOates) [86]. Seven of the furoxan based derivatives were tested for their in vitro cytotoxic activity against four cancer cell lines HCT116, Huh7, HepG2, and SW620, while the NONOates displayed negative result [86]. These derivatives can be lead compounds for further research.…”
Section: Pharmacological Activities Of Isosteviol Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Isosteviol 1 has moderate antihypertensive, 12 antihyperglycemic, 13 cardioprotective, 14 anti-tumor, 10 anti-tuberculosis, 15 and antimicrobial 16 effects. Chemical modification of isosteviol 1 did not only increase its antituberculosis, 15,[17][18][19] anti-cancer, 20,21 and anti-bacterial 22 activities but also provided it with antiviral, 23 antimitotic, 24 and mitochondriotropic 25 effects. It is interesting to note that although glycosylation of biologically active natural compounds that are not glycosides has long been considered as one of the ways to "tune their activity", 26 among more than 200 derivatives of isosteviol 1 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the cytotoxic activities of isosteviol derivatives have attracted much attention in recent years. In the previous study, the C-15 and C-16 functionalized isosteviol derivatives, obtained by means of group-conversion or structural modification exhibited good cytotoxic activities [17,18,19,20,21,22,23,24]. In view of the low cytotoxicity of isosteviol, it is suitable for the development of highly selective anticancer drugs by chemical modification [14,15,16].…”
Section: Introductionmentioning
confidence: 99%